The effect of anisotropy orientation on the sedimentary rock strength estimated by point load testing strength, Pilbara, Australia - Gao, X (Slope Stability 2020: 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Mine slope geotechnical design requires an engineering estimation of the intact rock’s uniaxial compressive strength, which is influenced by the anisotropic nature of sedimentary rocks. In order to determine the rock’s anisotropic behaviour, numerous rock samples from diamond drilling were tested in the field by using the point load test (PLT) method. The effect of anisotropy on the calculated point load strength ( from axial and diametral point load testing was investigated. The finding of this paper can be used to select σci input for the Hoek–Brown failure criteria based on low-cost PLT results.
Keywords: anisotropy index; point load test; point load strength; banded iron formation; shale